KEPEMIMPINAN DAN MANAJEMEN DALAM PENDIDIKAN - Amin Maulani (CV. Adiba Aisha Amira, 2024)
Many people believe that an organization will be effective if it is managed with good management. This opinion is not entirely correct, because leadership factors are what can move an organization to be effective. One of the factors that determines the success and sustainability of an institution or organization is whether the leadership is strong or not. The failure or success of an institution or organization is determined by the leader, because the leader is the controller and determiner of direction who can determine whether or not the organization's goals are achieved.